Psychopharmacology of moral and social judgments - Terbeck, S (2012)
This thesis is an interdisciplinary project in experimental social psychology, psychopharmacology, neuroscience, and neuroethics. The role of emotion in higher order psychological processes – social and moral judgments – was investigated. Specifically the role of noradrenergic mediated emotional arousal was researched. Behavioural studies demonstrated that acute beta adrenergic blockade with propranolol led to a reduction in negative implicit racial associations and also a modification of moral decision making. These findings suggest that basic affective processes might be causally relevant for higher order evaluations. However, enhancement with the noradrenergic potentiating agent reboxetine did not show effects opposite to those of propranolol on racial attitudes or moral judgments, which might indicate that emotional arousal, specific to beta-adrenoceptors might be involved in the effects of propranolol. Further a pharmacological fMRI study demonstrated that the activation pattern in brain regions commonly associated with intergroup bias -- such as the amygdala, insula, dorsolateral prefrontal cortex, and fusiform gyrus -- was affected by propranolol, and that the effect in the amygdala was correlated with implicit racial bias. Taken together the research suggests that automatic emotional arousal plays a role in higher order psychological processes, such as moral and social judgments, which aids the understanding of the underlying neurobiology of such processes. Finally, the ethical implications – such as the prospect of pharmacological moral enhancement – are discussed. The findings also suggest that the moral and social effects of already widely used psychotropic medications should be subject to further empirical and ethical investigation.